Rhinoplasty in Mestizo and Black Noses - Bernaldo Canto Vidal; Tania Canto Vigil (Medisur)
Background: There are many mestizos and black inhabitants in the Cuban population who from an economic stand-point, have a highly important percentage. Many of them feel the need to improve their faces aesthetically by means of the operative correction of their nose deformities known as rhinoplasty. Objective: To assess the results of rhinoplasties in mestizos and black patients. Methods: prospective study carried out in 52 mestizos and black patients who attended the Maxillo-Facial Surgery Outpatient of the University Hospital “Dr. Gustavo Aldereguía Lima” from 2006 to 2009. All mestizos were treated with an open technique in which three types of V incisions, inverted V and transversal V incisions were used. In the transoperative process 2cc of Triamsinolone were infiltrated, with the aim to avoid keloid formation and other techniques were combined with it. Digital photos were also used during the preparation of the cases either at the pre and post surgical stages as a way of evidencing the results. Results: 42 patients were mestizos, 20 of them were females and 22 males; 10 patients were black, 7 of them females and 3 males. All the patients were highly satisfied with the result of their surgery. There were no complications in these patients Conclusions: The use of the V technique for the surgical treatment of the mestizos and black noses is effective and the use of Triamsinolone avoids keloid formation.